Nurturing Children's Healthy Eating: Position statement. (1st June 2019) - Haines, Jess; Haycraft, Emma; Lytle, Leslie; Nicklaus, Sophie; Kok, Frans J.; Merdji, Mohamed; Fisberg, Mauro; Moreno, Luis A.; Goulet, Olivier; Hughes, Sheryl O.
Abstract: The relationship between eating a healthy diet and positive health outcomes is well known; nurturing healthy eating among children therefore has the potential to improve public health. A healthy diet occurs when one's usual eating patterns include adequate nutrient intake and sufficient, but not excessive, energy intake to meet the energy needs of the individual. However, many parents struggle to establish healthy eating patterns in their children due to the pressures of modern life. Moreover, healthcare providers often do not have the time or the guidance they need to empower parents to establish healthy eating practices in their children. Based on existing evidence from epidemiologic and intervention research, the Nurturing Children's Healthy Eating collaboration, established by Danone Institute International, has identified four key themes that encourage and support healthy eating practices among children in the modern Western world. The first — positive parental feeding — explores how parenting practices and styles, such as avoiding food restriction, allowing children to make their own food choices, and encouraging children to self-limit their portion sizes, can influence children's dietary intake. The second — eating together — highlights the link between eating socialization through regular family meals and healthful diet among children. The third — a healthy home food environment — explores the impact on eating practices of family resources, food availability/accessibility, parental modeling, and cues for eating. The fourth — the pleasure of eating — associates children's healthy eating with pleasure through repeated exposure to healthful foods, enjoyable social meals, and enhancement of the cognitive qualities (e.g. thoughts or ideas) of healthful foods. This paper reviews the evidence leading to the characterization of these nurturing themes, and ways in which recommendations might be implemented in the home.